Enhancing Rice Productivity and Soil Nitrogen Using Dual-Purpose Cowpea-NERICA® Rice Sequence in Degraded Savanna - Oikeh, S.; Niang, A.; Abaidoo, Robert C.; Houngnandan, P.; Futakuchi, K.; Koné, B.; Touré, A. (2012)
ISFM (integrated soil fertility management) involving annual sequencing of dual-purpose early-maturing first crop of cowpeas with biomass incorporation before seeding second crop of early-maturing NERICA® (New Rice for Africa) was evaluated to enhance rice productivity and soil-nitrogen. Five dual-purpose early-maturing cowpea cultivars and local cultivar (Katchè) were seeded early in the wet season in five farmers' fields at Ouake (9°46' N, 1°35' E, highly degraded-savanna), Benin. After pod harvest, cowpea residues were minimally worked into the soil using minimum tillage with hand-hoe and seeded with early-maturing, resilient NERICA8 rice that received either 20 kg N/ha or zero-N. Cowpea grain yield averaged 0.1-0.3 Mg/ha, and mean aboveground cowpea biomass produced and recycled was 0.54-0.64 Mg/ha among best cultivars (IT97-568-11 and IT89KD-288). NERICA8 seeded after cowpea cv. IT97-568-11 and supplied with 20N gave the greatest grain yield of about 2.0 Mg/ha, accounting for 500% heavier grains than fallow-rice rotation with zero-N. Mineral-N dynamics monitored under NERICA8 in year 2 showed that previous IT97-568-11 plots had the highest mineral-N at tillering which persisted till panicle initiation stage. The adoption of an ISFM comprising annual cowpea–NERICA sequence by smallholder rice farmers could enhance productivity and improve N-supply in fragile savannas.